PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Ika Kurnia; Fathurrahman Anwar (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to determine the Effect of Profitability and Capital Structure on Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX). Profitability uses return of equity (ROE), capital structure uses debt equity ratio (DER) and company value uses Tobin's Q. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2021. The samples used were 136 companies with the sampling technique using purposive sampling method. The analytical method used is multiple regression analysis using eviews. This study shows that paryially profitability and capital structure have a positive effect on firm value.